The effects and underlying mechanism of extracorporeal shockwave therapy on fracture healing - Lv, Fuxian; Li, Zhenlan; Jing, Yuling; Sun, Liyuan; Li, Zhiwei; Duan, Haoyang (Frontiers in Endocrinology, 2023)
The clinical efficacy of ESWT in treating bone non union has been widely recognized, but the biological mechanism of ESWT promoting bone non union healing is still unclear. ESWT can make old callus micro fracture through mechanical conduction, form subperiosteal hematoma, promote the release of bioactive factors, reactivate the fracture healing mechanism, rebalance the activities of osteoblasts and osteoclast, promote the angiogenesis of fracture site, and accelerate the healing of bone nonunion.Over recent years, great efforts have been made by both scientists and clinicians to explore the underlying mechanism behind the healing effect of ESWT on bone fractures. In this review, we introduced the growth factors during osteogenesis induced by ESWT hoping to provide new insights in the clinical use of ESWT.